Hemodynamic-Focused Anesthetic Strategy for Duodenal Atresia with Annular Pancreas in a Low-Birth-Weight Neonate: A Case Report and Pathophysiological Review - Anggia Rarasati Wardhana; Ardana Tri Arianto; Heri Dwi Purnomo (HM Publisher, 2025)
Introduction: The anesthetic management of low-birth-weight (LBW) neonates with complex congenital anomalies like duodenal atresia presents a profound physiological challenge. These patients exhibit immature organ systems, precarious fluid balance, and heightened sensitivity to anesthetic agents. This case report describes a successful hemodynamically-focused anesthetic strategy in a particularly high-risk neonate with the combined pathology of duodenal atresia and a constricting annular pancreas. Case presentation: A 4-day-old, 1800-gram male infant, born at 37 weeks with intrauterine growth restriction, presented with prenatally diagnosed duodenal atresia. Preoperative stabilization focused on correcting a severe hypochloremic, hypokalemic metabolic alkalosis. A hemodynamically stable anesthetic induction was achieved using intravenous fentanyl (2.8 mcg/kg) and ketamine (2.8 mg/kg), avoiding myocardial depressant volatile agents. Anesthesia was maintained with 60% oxygen in air and intermittent opioid boluses. Intraoperative management was centered on meticulous, goal-directed fluid therapy, rigorous maintenance of normothermia, and lung-protective ventilation. The surgery, a duodenojejunostomy, was completed successfully with remarkable hemodynamic stability. The infant was transferred to the NICU for planned postoperative ventilation and was extubated on the second postoperative day. Postoperative analgesia was achieved with a continuous sub-anesthetic ketamine infusion, later transitioned to intermittent metamizole. Conclusion: The successful outcome in this fragile neonate underscores the value of a tailored anesthetic approach grounded in neonatal pathophysiology. A strategy utilizing hemodynamically stable induction agents, proactive correction of metabolic derangements, goal-directed fluid therapy, and a planned, staged recovery can effectively mitigate the significant perioperative risks associated with major abdominal surgery in LBW infants with complex congenital anomalies.